Top 100 careers without a four-year degree [ your complete guidebook to good jobs in many fields - Shatkin, Laurence; Farr, J. Michael (Indianapolis, Indiana : JIST Works, 2012)
In a book that covers the one hundred best careers for those with only a high school degree, the authors cover how to research careers and learn about pay; job outlook through 2018; education and skills for each job; how to match one's personal skills to the careers; and seven steps for landing a great job in no time.
1. Using the job-match grid to choose a career -- 2. Descriptions of the top 100 careers without a four-year degree -- 3. Quick job search -- 4. Important trends in jobs and industries
Includes index
Keywords: Employment forecasting -- United States; Job hunting -- United States; Occupations -- United States; Vocational guidance -- United States